A systematic review of flotation-restricted environmental stimulation therapy (REST) - Elnaz Lashgari; Emma Chen; Jackson Gregory; Uri Maoz (BMC Complementary Medicine and Therapies)
Abstract Background Restricted Environmental Stimulation Therapy (REST) is a therapeutic technique that involves immersing an individual in an environment with minimal sensory input or stimulation. The goal of REST is to induce a state of relaxation that is deeper than what can be achieved through other forms of relaxation techniques. Research suggests that REST can help reduce anxiety, alleviate chronic pain, improve sleep, and enhance creativity and cognitive function. Flotation-REST is a popular type of REST that utilizes an enclosed tank filled with buoyant saltwater to facilitate relaxation. This study aimed to synthesize the evidence on studies that investigate the effects of flotation-REST. Methods We used Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) to survey the flotation-REST literature starting from the earliest papers we could find, in 1960, until May 2024. This search was conducted on 23 May 2024 within the Google Scholar and PubMed databases. Journal and conference papers, as well as electronic preprints, that used flotation-REST in their methods, and that were written in English were included; non-original research papers (e.g., review papers, book chapters, and papers solely on types of REST other than flotation-REST (e.g., chamber-REST) were excluded. From each eligible paper, we extracted information regarding the participant sample, application of flotation-REST, experimental design, treatment delivery method, questionnaires and tools, and study results. Results In total, we found 63 studies that included 1,838 participants. We propose that the application of flotation-REST can be divided into nine main categories: pain, athletic performance, physiology, stress, consciousness, psychology, creativity, clinical anxiety, sleep, smoking cessation, and other miscellaneous applications. In general, flotation-REST was found to bring about positive effects on pain, athletic performance, stress, mental well-being, and clinical anxiety, while having limited to no effect on sleep-related disorders and smoking cessation. Conclusion This paper provides a comprehensive overview of the current research on flotation-REST, highlights ongoing limitations in the literature, and outlines potential areas for future research. While flotation-REST appears to induce various benefits for physical and mental well-being, particularly when it comes to managing states like pain and stress, more research is needed to better understand the mechanisms underlying these effects and to identify optimal treatment protocols for different populations. A limitation of this paper is the relatively small number of studies available for review, which limits the generalizability of certain findings and highlights the need for additional research in this area.